Photoassociation in Cold Atoms via Ladder Excitation - Trachy, M. L.; Veshapidze, G.; Shah, M. H.; Jang, H. U.; DePaola, B. D. (My University, 2007)
We explore 2-color photoassociative ionization in cold Rb vapor and present experimental evidence that the molecular ions are produced from the stepwise excitation of a ladder of molecular states. We also explore a new process, dubbed photoassociative-dissociative ionization, by which atomic ions are created by excitation through a ladder of molecular states, finally autoionizing to a dissociative potential curve of Rb+2. We submit that these experiments could be the starting point for the same sort of high resolution spectroscopy that has already been done for lower electronic states of cold Rb2 at large internuclear separation.